An improvement of Chalet Management System - Xiu, Ting Lim; Lee, Khai Loon (Penerbit UMP, 2020)
The constant growth of the tourism industry in Malaysia has led to the rise of the hospitality industry over recent years. The major tourism SMEs are usually providing the needs or demand of touristy to tourists such as food, accommodation, transportation and other necessities. This paper focuses on the issues of poor customer satisfaction and operational performance that occur in a small and medium scale hospitality company and the ways to solve the problem by developing a prototype of the Chalet Management System. The five whys analysis was used to identify the problems that occur in the hospitality company. The prototype of the Chalet Management System is developed by using Rapid Application Development (RAD) technique with Microsoft Access. This study showed that the Chalet Management System had improved customer satisfaction and operational performance by decreasing the registration process lead time and improving data accuracy and efficiency. The proposed system also received positive feedbacks with its functionalities from the company